Temporal Trends in the Outcomes of Dialysis Patients Admitted With Acute Ischemic Stroke. Issue 12 (19th June 2018) - Alqahtani, Fahad; Berzingi, Chalak O.; Aljohani, Sami; Al Hajji, Mohamed; Diab, Anas; Alvi, Muhammad; Boobes, Khaled; Alkhouli, Mohamad
Abstract : Background: There is a paucity of contemporary data on the characteristics and outcomes of acute ischemic stroke (AIS) in patients on maintenance dialysis. Methods and Results: We used the nationwide inpatient sample to examine contemporary trends in the incidence, management patterns, and outcomes of AIS in dialysis patients. A total of 930 010 patients were admitted with AIS between 2003 and 2014, of whom 13 642 (1.5%) were on dialysis. Overall, the incidence of AIS among dialysis patients decreased significantly ( P trend <0.001), while it remained stable in non‐dialysis patients ( P trend =0.78). Compared with non‐dialysis patients, those on dialysis were younger (67±13 years versus 71±15 years, P <0.001), and had higher prevalence of major comorbidities. Black patients constituted 35.2% of dialysis patients admitted with AIS compared with 16.7% of patients in the non‐dialysis group ( P <0.001). After propensity score matching, in‐hospital mortality was higher in the dialysis group (7.6% versus 5.2%, P <0.001), but this mortality gap narrowed overtime ( P trend <0.001). Hemorrhagic conversion and gastrointestinal bleeding rates were similar, but blood transfusion was more common in the dialysis group. Rates of severe disability surrogates (tracheostomy, gastrostomy, mechanical ventilation and non‐home discharge) were also similar in both groups. However, dialysis patients had longer hospitalizations, and accrued a 25% higher total cost of acute care. Conclusions: Dialysis patients have 8‐folds higher incidence of AIS compared withnon‐dialysis patients. They also have higher risk‐adjusted in‐hospital mortality, sepsis and blood transfusion, longer hospitalizations, and higher cost. There is a need to identify preventative strategies to reduce the risk of AIS in the dialysis population.